Bibliometrics services and academic libraries: Towards transparency - González-Fernández-Villavicencio, Nieves (Anuario ThinkEPI, 2017)
Bibliometric services are being consolidated in the Spanish academic field due to growing interest in academic performance by university managers and leaders. Academic librarians are a key part of the bibliometric services because of their expertise in providing support and training to researchers and advice in research assessment. Bibliometric services functions and the current landscape of bibliometric services in Spain are described.
Keywords: Bibliometrics services; Bibliometrics; Academic libraries; Research support; Research.